Aplikasi dosis mikorhiza dan zat pengatur tumbuh indole butiric acid terhadap hasil tanaman jeruk siam (Citrus nobilis var microcarva L.) - Senon Apriyanto Nahak; Ni Komang Alit Astiari; Luh Kartini (GEMA AGRO, 2018)
This study aims to determine the effects of mycorrhizal and indole butyric acid (IBA) growth regulators and their interactions on siam citrus products. This study uses a randomized block design (RBD) with two factors arranged factorially. The first factor to be tried was the mycorrhizal dose which consisted of 3 levels, namely 0, 50, and 100 g/plant, while the second factor tried was the concentration of the substance indole butiric acid (IBA) growth regulator consisting of 4 levels, namely 0, 50, 100, and 150 ppm/plant. Thus there are 12 combination treatments, each of which is repeated 3 times so that 36 citrus trees are needed. The results showed that the interaction between mycorrhizal dose and the concentration of IBA had no significant effect on all observed variables. Treatment of mycorrhizal doses and dosage of IBA had a very significant effect on the weight of harvested fruit per tree. The highest yield of fruit per tree was obtained in 100 g / plant mycorrhiza treatment, which was 13.53 kg, an increase of 57.88% compared to the lowest yield in mycorrhiza treatment, which was 8.57 kg. The highest yield of fruit per tree was obtained at IBA concentration of 100 ppm / plant, which was 15.03 kg, an increase of 78.08% compared to the lowest yield on IBA concentration without 8.44 kg.